Acute Phase Response and Postprocedural Evaluation of Open and Laparoscopic Cryoablation Procedures in Porcine Pancreases. Issue 9 (October 2020) - Imai, Shunichi; Kitago, Minoru; Matsuda, Sachiko; Nakamura, Yuki; Shinoda, Masahiro; Yagi, Hiroshi; Abe, Yuta; Fujita, Yusuke; Nakano, Yutaka; Iwata, Kansei; Nakatsuka, Seishi; Kitagawa, Yuko
Abstract : Objectives: Cryoablation is a potentially less invasive locoregional ablation modality. Although cryoablation has been used to treat malignancy in various organs, a limited application of this modality in the pancreas has been reported. Methods: Acute phase response assessments and postprocedural course evaluations of 2 experimental locoregional ablation methods were conducted. In one method, open and laparoscopic cryoablation of a porcine pancreas using an argon-helium gas–based cryoablation system and monitoring of tissue temperature during the procedure were performed. In the other method, open cryoablation of a porcine pancreas using liquid nitrogen was performed. The animals were evaluated postoperatively. Results: The size of the cryolesion was larger in the second treatment than in the first. Laparoscopic cryoablation was associated with the formation of an iceball, which possibly affected the surrounding structures. The ablated region was adequately cooled with 10 minutes of freeze/repeat cycles. The area cooled to a temperature of less than −40°C was approximately half the size of the cryolesion in diameter. The swine used for the evaluation of the postprocedural course survived 3 weeks after the procedure with a temporal elevation of the serum lipase level. Conclusions: Cryoablation of the pancreas was experimentally practicable without severe complications under direct or laparoscopic vision.